KUALITAS FISIK WAFER RANSUM KOMPLIT MELALUI PENAMBAHAN KULIT BUAH KAKAO FERMENTASI YANG DISIMPAN DENGAN JENIS KEMASAN DAN WAKTU YANG BERBEDA - Muhammad Affan Amin Nasution; Anwar Efendi Harahap; Edi Erwan (Jurnal Ilmu dan Teknologi Peternakan, 2021)
The use of packaging wafer is one way to protect feed from various factors that can cause a decrease in the quality of the stored feed. Storage aims to maintain and preserve stored commodities by avoiding, eliminating various factors that can reduce the quality and quantity of the commodity. This study uses a completely randomized factorial design (5 x 3) with 3 replications. Factor A is the type of packaging consisting of A0 = without packaging, A1 = packaging bags  of rice, A2 = packaging bags  of plastic, A3 = packaging bags  of papers, A4 = packaging bags of sacks. Factor B is the storage time  B0 = 0 days B1 = 14 days B2 = 28 days. The parameters were the texture, color, aroma, water absorption, density. The results showed that there was an interaction between different types of packaging and storage duration of the texture, color, aroma and density of the complete wafer skin of fermented cocoa pods with different types of packaging and storage time. The type of rice sack packaging with 14 days storage time produces the best physical wafer quality compared to other treatment combinations seen from the texture of water absorption and density